2016
DOI: 10.2134/agronj2016.01.0046
|View full text |Cite
|
Sign up to set email alerts
|

Rotation Impact on On‐Farm Yield and Input‐Use Efficiency in High‐Yield Irrigated Maize–Soybean Systems

Abstract: Cereal yields tend to be higher in cereal–legume rotations relative to cereal monoculture yields. We investigated the influence of crop rotation on yield and input‐use efficiency in high‐yield irrigated maize (Zea mays L.)‐based cropping systems using producer‐reported data from western U.S. Corn Belt (about 11,000 observations). Across regions, average yield of maize grown after soybean [Glycine max (L.) Merr.] (S–M) was 0.2 to 0.6 Mg ha−1 (2–5%) higher, relative to yield of maize grown after maize (M–M). Soy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…Averaged across the 5 yr, the yields for soybean grown once every 3 yr were greater (+0.20 Mg ha −1 ) than those for S‐S‐S, whereas the 2‐yr C‐S rotation resulted in intermediate yields. Our results agree with soybean yields reported in Iowa and Nebraska after 2 consecutive years of corn (Al‐Kaisi et al, 2016; Farmaha et al, 2016). In addition, several studies indicated that, in most situations, soybean grain yield was improved (+0.40 Mg ha −1 on average) when the C‐S rotation was diversified with winter wheat (Gaudin et al, 2015b; Marburger et al, 2015; Kazula and Lauer, 2018).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Averaged across the 5 yr, the yields for soybean grown once every 3 yr were greater (+0.20 Mg ha −1 ) than those for S‐S‐S, whereas the 2‐yr C‐S rotation resulted in intermediate yields. Our results agree with soybean yields reported in Iowa and Nebraska after 2 consecutive years of corn (Al‐Kaisi et al, 2016; Farmaha et al, 2016). In addition, several studies indicated that, in most situations, soybean grain yield was improved (+0.40 Mg ha −1 on average) when the C‐S rotation was diversified with winter wheat (Gaudin et al, 2015b; Marburger et al, 2015; Kazula and Lauer, 2018).…”
Section: Resultssupporting
confidence: 92%
“…This agrees with the recent study of Al‐Kaisi et al (2015) in Iowa, who found that a 10‐yr C‐S rotation resulted in greater corn yields than C‐C‐C or C‐C‐S. Farmaha et al (2016) also reported an average yield increase of 0.2 to 0.6 Mg ha −1 for corn grown after soybean compared with C‐C‐C when compiling producer‐reported data (11,400 observations) from irrigated fields in Nebraska. In Wisconsin, Kazula and Lauer (2018) reported that corn in a 3‐yr rotation with soybean and winter wheat yielded 1.5 and 0.9 Mg ha −1 more than C‐C‐C or C‐S rotation, respectively.…”
Section: Resultssupporting
confidence: 91%
“…However, important improvements in productivity also are likely to come from innovations at the cropping or farming system levels ( Rodriguez and Sadras, 2011 ). In temperate rainfed agriculture, where rainfall and temperature constrain the system to a single crop per year, crop rotations are particularly relevant to farm-level production ( Angus et al, 2015 , Farmaha et al, 2016 ). In environments with a longer growing season where multiple cropping is feasible, capture of resources and yield are often improved through the processes of facilitation and niche differentiation in time and space ( Brooker et al, 2014 , Gaba et al, 2014 , Li et al, 2007 , Malézieux et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that following 14 years of continuous corn, soybeans had a higher yield when compared with the other preceding crop sequences. A recent study conducted by Farmaha, et al 51 stated that soybean yield in an irrigated corn-corn-soybean rotation was higher than in a soybean-corn-soybean rotation. The results from our study expanded the conclusion that two or more previous years of corn crop sequences resulted in increased soybean yield as compared to one previous year of corn crop sequences.…”
Section: Discussionmentioning
confidence: 98%